1993
DOI: 10.1254/jjp.63.181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of D-Ala2-D-Leu5-Enkephalin, Microinjected into the Supraoptic and Paraventricular Nuclei, on Urine Outflow Rate

Abstract: ABSTRACT-The effects of D-Ala2-D-Leu5-enkephalin (DADL, a o-opioid agonist), microinjected directly into the hypothalamic supraoptic (SON) and paraventricular (PVN) nuclei, on urine outflow rate, urinary osmotic pressure, blood pressure, heart rate, respiratory rate and rectal temperature were investigated in water-loaded and ethanol-anesthetized rats. The microinjection of DADL into both the nuclei decreased urine outflow rate in a dose-dependent manner with an increase in urinary osmotic pressure, but did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The microinjec tion of oxotremorine and D-A1a2-D-Leu5-enkephalin pretreated with the vasopressin antagonist did not elicit any effects on the urine outflow rate (20,21). The vasopressin antagonist alone did not significantly change the rate.…”
Section: Effects Of Antagonists On Ang Ii-induced Antidiuresesmentioning
confidence: 83%
See 1 more Smart Citation
“…The microinjec tion of oxotremorine and D-A1a2-D-Leu5-enkephalin pretreated with the vasopressin antagonist did not elicit any effects on the urine outflow rate (20,21). The vasopressin antagonist alone did not significantly change the rate.…”
Section: Effects Of Antagonists On Ang Ii-induced Antidiuresesmentioning
confidence: 83%
“…Our previous studies (17)(18)(19)(20) show that adrenergic and cholinergic mechanisms of urine production in the SON and PVN are similar to each other. However, as for opioid mechanisms, which are probably mediated through o and a-subtypes, the PVN seems to involve more potent regulation than the SON (21,22). Cooperation on urine production between the bilateral SON and PVN is interesting.…”
Section: Effects Of Antagonists On Ang Ii-induced Antidiuresesmentioning
confidence: 99%
“…Because the serotonin antagonist metergoline suppressed the increased urine due to cyclazocine or U50,488 (174), it was suggested that serotonin might be involved in the complex mechanism of K agonist-induced diuresis (174). The effect of microinjection of DADLE into the paraventricular nucleus or supraoptic nucleus was similar to that for dynorphin, with only the former producing an opiate-mediated effect and with an interaction between opiate, adrenergic, and cholinergic mechanisms at both sites (517). Naloxone alone (238) and naltrindole during naloxone-precipitated withdrawal from butorphanol (250) had no effect on urine output, leading to questions concerning the involvement of the opiate system in its normal regulation.…”
Section: Gastrointestinal Renal and Hepatic Functionsmentioning
confidence: 99%
“…Similarly, the effects of the 6 agonists were highly variable, producing hypotension (23) or not changing after DADLE (517) and producing hypertension after DPDPE (414). DADLE raised systolic pressure when administered to epicardial ganglia (23) but had no effect when microinjected into the supraoptic nucleus or paraventricular nucleus (517), so that the site of injection was crucial for these agonists, too. The mixed agonist/antagonist pentazocine also had a pressor effect (402).…”
Section: Cardiovascular Responsesmentioning
confidence: 99%
“…Besides affecting GI motility, opioid receptors including DORs have also been implicated in renal function (Holt et al 2005; Sezen et al 1998). It is thought that these effects can be attributed to stimulation of peripheral opioid receptors on kidney cells by enkephalins released from the parasympathetic ganglia (de Groat and Kawatani 1989) as well as effects mediated by DORs in the paraventricular and hypothalamic supraoptic nuclei (Tsushima et al 1993). …”
Section: Introductionmentioning
confidence: 99%